WHAT DOES IT MEAN TO THINK PEDAGOGICALLY TODAY? - A. A. POLONNIKOV (Высшее образование в России)
The paper presents a commentary on the article “Pedagogical knowledge and a scholarly text reflecting it in the realities of the “semiological turn” (a dialogue with A.A. Polonnikov)” by A.V. Korzhuyev and N.N. Antonova. The author analyzes the basic metaphors constituting the current pedagogical discourse and discusses the issue concerning the linking between pedagogical research and pedagogical practice. The paper comes to a conclusion about their inseparable unity, as well as about the multiplicity of research forms and pedagogies immanent to them. The author introduces an idea of the modern pedagogical thinking. Its main characteristic is the change of self-consciousness of the pedagogical language as a leading condition of educational relationships’ operation and development.